Synthesis, Characterization, and Photocatalytic Properties of Sulfur- and Carbon-Codoped TiO(2) Nanoparticles - Ivanov, S. (Nanoscale Res Lett, 2016)
One-step TiO(2) nanoparticle synthesis based on the interaction between thiourea and metatitanic acid is applied for sulfur and carbon anatase codoping. The synthesis of the doped TiO(2) has been monitored by means of differential thermal analysis and thermogravimetric analysis (DTA-TG), which allows determining the optimal thermal conditions for the process. Electron microscopy showed micrometer-sized (5–15 μm) randomly distributed crystal aggregates, consisting of many 15–40-nm TiO(2) nanoparticles. The obtained phase composition and chemical states of the doping elements are analyzed by means of X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), infrared (IR) and Raman spectroscopies, and electron paramagnetic resonance (EPR). XRD displays in both samples (doped and pristine) the existence of only one crystalline phase—the tetragonal modification of TiO(2)—anatase. Further data assessment by means of Rietveld refinement allowed detection of a slight c lattice parameter and volume increase related to incorporation of the doping elements. XPS demonstrated the presence of carbon and sulfur as doping elements in the material. It was confirmed that carbon is in elemental form and also present in oxygen-containing compounds, which are adsorbed on the particle surface. The binding energy for sulfur electron core shell corresponds to the established data for sulfate compounds, where sulfur is in 6+ oxidation state. The synthesized S- and C-codoped TiO(2) showed excellent photocatalytic performance during the degradation of organic dyes (rhodamine B, methylene blue), gas-phase oxidation of ethanol under visible light, and photocatalytic hydrogen generation from ethanol under ultraviolet light. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s11671-016-1353-5) contains supplementary material, which is available to authorized users.